2016
DOI: 10.1111/padm.12264
|View full text |Cite
|
Sign up to set email alerts
|

Designing Resilient Institutions for Transboundary Crisis Management: A Time for Public Administration

Abstract: Crises and disasters feature high on political and public agendas around the world. Practitioners wrestle with the challenge to provide protection while maintaining legitimacy. They pine for insights that lie at the heart of public administration: designing effective institutions and preserving transparency; enabling and empowering citizens without undermining a coordinated response; balancing long-term risks against short-term needs; bridging the divide between theory and practice, and between the public and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
153
0
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(176 citation statements)
references
References 51 publications
(33 reference statements)
1
153
0
22
Order By: Relevance
“…Further, the issue of coordination seems to be central (van der Vegt et al, ). Especially with regard to transboundary crises (Boin & Lodge, ; Hermann & Dayton, ), we see the emergence of spontaneous response groups, which create new challenges for efficient coordination (Beck & Plowman, ; Majchrzak, Jarvenpaa, & Hollingshead, ; Williams & Shepherd, ). Not only do crises impact associated organizations due to those organizations’ deep embeddedness in organizational networks, but recovery also requires additional organizations to join these networks to bring in additional resources.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…Further, the issue of coordination seems to be central (van der Vegt et al, ). Especially with regard to transboundary crises (Boin & Lodge, ; Hermann & Dayton, ), we see the emergence of spontaneous response groups, which create new challenges for efficient coordination (Beck & Plowman, ; Majchrzak, Jarvenpaa, & Hollingshead, ; Williams & Shepherd, ). Not only do crises impact associated organizations due to those organizations’ deep embeddedness in organizational networks, but recovery also requires additional organizations to join these networks to bring in additional resources.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…Forsking på dette området, og saerleg innafor statsvitskapen, har vore mangelfull og etterlyst (Boin og Lodge 2016), men har etter kvart og fått fotfeste innafor feltet offentleg politikk og administrasjon med vekt på organisering og studiar av administrative reformer (Christensen mfl. 2016a, Christensen mfl.…”
unclassified
“…Forskinga om korleis ein kan designe institusjonar i offentleg forvaltning for å verne borgarane mot grenseoverskridande trugsmål og samanbrot i kritisk infrastruktur er mangelfull (Boin og Lodge 2016). Den statsvitskapelege forskinga har vore nokså taus når det gjeld korleis ein organiserer seg for å møte slike truslar, og kva konsekvensane er av dei vala ein tek.…”
unclassified
“…Scientists emphasize that a mixture of new threats and accruing vulnerabilities undermine the stability and prosperity of modern societies to a high extent (Boin & Lodge, 2016;Kuipers et al, 2015). Unseen complexity and tight coupling of critical infrastructures are considered the main drivers of unanticipated events which can hardly been controlled (OECD, 2011;Perrow C., 1984).…”
Section: Ongoing Disaster Researchmentioning
confidence: 99%
“…The academics also found that the public administration community has been very absent up to now in the debates about designing institutions that protect against mega-crises. Therefore, they argue that the time has come for public administration researchers to incorporate disaster management into their research agenda (Boin & Lodge, 2016).…”
Section: Ongoing Disaster Researchmentioning
confidence: 99%